SEXUAL PRACTICES IN GEOLOCATION BETWEEN MEN'S: BODIES, PLEASURES, TECHNOLOGIES - Couto, Walter; Morelli, Fabio; Galindo, Dolores; Souza, Leonardo Lemos de (Univ Autonoma Barcelona, 2016)
Locative media, geolocation applications, as well as homosocialization web spaces are problematized so as to promote some separation from the traps of normalization and pathologization. These unfold themselves into prosthetic pleasures that take their place in the experiencing of bodies and of their multiplicity linked to technologies of (de)territorialization. We question how Psychology can think of concepts/devices towards the new sexes/genders/pleasures of digital social networks and towards the normative traps that pose themselves at the interactions of these spaces.
Keywords: Locatives Midias; Social Networks; Sexual Practices; Homosocialities